“Sleep” Subtype of Rest Verbs in English and Buginese: Dixon’s Theoritical Framework - Wahyuningsi Fahrah; Abdul Hakim Yassi; Sukmawaty Sukmawaty (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
The aims of this research are (1) To identify rest verbs in English and Buginese based on Dixon's classification of sleep subtypes. (2) To examine the distinctions and equivalences between the English and Buginese Sit subtypes of Rest verbs in terms of semantics and grammatical structure. While the data for Buginese were gained from field research through the process of observation and in-depth interview, the data for English were taken from the Corpus of Contemporary American English (COCA). Both sets of data were evaluated using qualitative and descriptive methods. This study's findings demonstrate that (1) there are six rest verbs of Sleep subtype in English, they are sleep, nap, doze, siesta, drowse, catnap, and beauty sleep. While in Buginese, there are many verbs that refers to rest verb, they are Tinro’, lewu’, makkapeddeng’,cakkaruddu’,  mappalempu’, moppang’, lengeng’, nDitti’, manippi’, mappasau’ tengngeng’, maggalelu’ mangkangulu’, makkadukku’, maggalengkeng’, mappalangka’, mabboco’, ma’ranjang, maggalampang’, rebba’-rebba’, lesso’, mammauneng’, mangoro’and mabbenni’. (2) Clause structure and stance of resting are two areas where the main distinctions between rest verbs in English and Buginese based on the Sleep subtype may be recognized. According to clause structure, an NP in English is followed by a VP, however in Buginese it is acceptable for a VP to be followed by an NP that is denoted by the prefix Ma'- in VP. From the perspective of the resting aspect, cultural background has a significant impact on the different rest verb forms. Keywords: Preposition, locus, culture, rest verbs, semantic verb kinds.